Seminal plasma protein profile based on molecular weight and their correlation with semen quality of Simmental bull - Baharun, A.; Arifiantini, I.; Karja, N. W. K.; Said, S. (Diponegoro University, 2021)
Artificial Insemination Center (AIC) produces frozen semen that was taken from superior bull. The selection of superior bull was based on breeding soundness evaluation. This study is aimed to evaluating the correlation between the molecular weight (MW) of seminal plasma protein and semen quality of Simmental bulls. Semen ejaculates from nine Simmental Bulls, that belong to AIC of Central Java, at Ungaran, were collected by using an artificial vagina. The sub population of sperm in ejaculates was evaluated through macroscopically and microscopically, in which the semen then centrifugated 6500 rpm for 30 minutes. The supernatant was collected and inserted into mini straw and stored in liquid nitrogen container. The concentration of seminal plasma protein was determined by the Bradford method. The Bradford protocol of analysis was suitable with User Guide Coomasize (Bradford) Protein Assay Kit. Thermo Skanlt RE for Multiskan Go Software, 3.2 version was applied for analyzing of the data, and protein characterization used was 1D-SDS-PAGE. The Coomassie Brilliant Blue was used for coloring the gels, and the proteins MW was determined by MW markers. The result demonstrated that there was no significant correlation between protein concentration and semen quality (P>0.05). Protein expressions based on MW were 62-48 kD, 100-71 kD found in this study. The analysis of correlation showed that the proteins with 100-71 kD MW correlated with sperm motility, normal sperm morphology, and sperm concentration. Semen quality in all parameters was significant (P˂0.05 and P>0.01) with 62-48 kD protein MW. The result concluded that seminal plasma protein had a correlation with semen quality and can be used as additional indicator for bull’s candidate selection.